Chinese Firms’ Integration Approaches in Their Overseas Mergers & Acquisitions in Developed Economies: Case Studies in Europe - Song, T.; Ma, S.; Hao, S. (The Ninth International Symposium on Multinational Business Management-- Entrepreneurship, Organizational Change and Employment Management, 2017)
Since the global financial crisis of 2007-2008, an increasing number of Chinese firms have been engaged in cross-border mergers and acquisitions (M&As), particularly in developed economies. However, research about Chinese cross-border M&A is rather limited?compared with numerous studies on M&As by firms from developed countries. As the institutional environments and markets of developed economies are significantly different from China, the integration approaches adopted by acquiring firms from developed economies may not be applicable for Chinese firms that grow and develop in an emerging economy. Thus this study aims to address the following fundamental question: how do Chinese companies integrate their overseas subsidiaries in the post M&As in developed economies? This article provides a thorough literature review of the integration approaches by developed economies and emerging economies. Consequently, we identify the characteristics of Chinese cross-border M&As integration approaches in developed countries. In general, Chinese acquirers tend to use light-touch approach and partnering approach. We discuss the above findings with Chinese M&A cases in Europe. This study contributes to the small but growing body of research on Chinese firms’ cross-border acquisitions and provide implications for the success of post M&A integration for both Chinese firms and firms from similar emerging economies in their cross-border acquisitions.